2012
DOI: 10.1007/s00405-012-2198-x
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to subperiosteal orbital abscesses

Abstract: The purpose of this paper is to evaluate the epidemiology, clinical features, management and complications of subperiosteal orbital abscesses (SPOA)-a serious complication of rhinosinusitis. Retrospective data of 36 patients with SPOA secondary to acute rhinosinusitis from January 1998 to December 2011 were evaluated. Patients were analyzed in terms of age, gender, clinical features, CT findings, surgical procedures, microbiology, and complications. Twenty-three males and 13 females aged from 3 to 76 were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
2
28
0
5
Order By: Relevance
“…The orbital complications, as a result of the spread of infection from the sinuses to adjacent tissues, are the most frequent complications, which accounts for about 80% of all complications. If the treatment is not correct and in time, orbital complications could progress rapidly, leading to optic neuritis, cavernous sinus thrombophlebitis or life-threatening intracranial complications (2,3). In order to explore the correct treatment of orbital complications secondary to acute rhinosinusitis, a retrospective analysis of 31 pediatric patients with orbital complications was made in our hospital.…”
mentioning
confidence: 99%
“…The orbital complications, as a result of the spread of infection from the sinuses to adjacent tissues, are the most frequent complications, which accounts for about 80% of all complications. If the treatment is not correct and in time, orbital complications could progress rapidly, leading to optic neuritis, cavernous sinus thrombophlebitis or life-threatening intracranial complications (2,3). In order to explore the correct treatment of orbital complications secondary to acute rhinosinusitis, a retrospective analysis of 31 pediatric patients with orbital complications was made in our hospital.…”
mentioning
confidence: 99%
“…The advent of the Pneumococcal and H. influenzae type b (HiB) vaccinations have reduced the incidence of streptococci 15,16 and HiB; however, this has correlated with an increased incidence of S. aureus as well as methicillin‐resistant S. aureus (MRSA), 15‐17 not only in SPAs but also in rhinosinusitis 17 . It is also thought that this has been associated with an increase in cases of S. milleri – S. anginosus group and S. pyogenes 13,16,18,19 . Anaerobic organisms or oropharyngeal flora are also commonly detected.…”
Section: Discussionmentioning
confidence: 99%
“…The mean interval between admission to ENT unit and surgical intervention was 1.26 days.The symptoms at presentation included fever in 73.7% (14), periorbital swelling in 90% (16), eye pain in 63.2% (12), history of upper respiratory tract infection in 68.4% (13) and epiphora in 63.2% (12). Visual loss or a relative afferent papillary defect was not present in any of the patients.Signs included chemosis in 68.4% (13), proptosis in 57.9% (11) and ophthalmoplegia in 42.1% (8).Chemosis was found in 62% of the patients with intra-orbital abscesses, showing a statistically significant association. Ophthalmoplegia was seen in 37% of the patients with intra-orbital abscesses, but did not show a statistically significant association.…”
Section: Figure 2-unit Of First Contactmentioning
confidence: 98%
“…Various studies have suggested criteria for conservative management including age less than 9 years, medially located small subperiosteal abscess (less than 10mm), no suspicion for anaerobic infection or dental origin, no suspicion of frontal sinusitis, no chronic sinusitis and normal vision, pupil & retina, no ophthalmoplegia, intraocular pressure < 20mmhg and proptosis of less 5mm [12,13,14,15] .…”
Section: Organisms Culturedmentioning
confidence: 99%
See 1 more Smart Citation